A Comparative Analysis of Individual RAS Mutations in Cancer Biology - Muñoz-Maldonado, Carmen; Zimmer, Yitzhak; Medová, Michaela (Frontiers in Oncology, 2019)
In human cells, three closely related RAS genes, termed HRAS, KRAS and NRAS, encode four highly homologous proteins. RAS proteins are small GTPases involved in a broad spectrum of key molecular and cellular activities, including proliferation and survival among others. Gain-of-function missense mutations, mostly located at codons 12, 13 and 61, constitutively activate RAS proteins and can be detected in various types of human cancers. KRAS is the most frequently mutated, followed by NRAS and HRAS. However, each isoform exhibits distinctive mutation frequency at each codon, supporting the hypothesis that different RAS mutants may lead to distinct biologic manifestations. This review is focused on the differences in signaling and phenotype, as well as on transcriptomics, proteomics and metabolomics profiles-related to individual RAS-mutated variants. Besides, association of these mutants with particular targeted outcomes and rare mutations at additional RAS codons are discussed.